Culture and Literary Criticism in the 1930s and '40s.The Case of F.R. and Q.D. Leavis - Jean-Christophe MURAT (E-REA)
This article offers a revaluation of the position of the two famous Cambridge critics F.R. and Q.D. Leavis in twentieth-century literary studies, with particular reference to the 1930s and '40s. It will look first to F.R. and Q.D.'s relations with each other and with other major Cambridge academics of the 1920s and '30s, before analysing the Leavises' vexed but constant relationships with the world of the print media, and asking whether they should be regarded as proper critics, or as mere representatives of a higher form of journalism. All along the argument will be guided by the implicit - or sometimes explicit - distinction between two conceptions of culture and criticism: one that simply views the teaching of literature as the handing down of a set of dates, canonical names and consensual judgments; the other that considers that this teaching should exert a decisive influence on one's perception of human culture and history, and induce a collaborative form of social life. Finally this study will try to analyse why, in some respects, F.R. and Q.D. Leavis's academic achievements fell short of their initial ambitions.